The God of Small Things
The year is 1969. In the state of Kerala, on the southernmost tip of India, a skyblue Plymouth with chrome tailfins is stranded on the highway amid a Marxist workers\\\' demonstration. Inside the car sit two-egg twins Rahel and Esthappen, and so begins their tale.... Armed only with the invincible innocence of children, they fashion a childhood for themselves in the shade of the wreck that is their family - their lonely, lovely mother, Ammu who loves by night the man her children love by day, their blind grandmother, Mammachi who plays Handel on her violin, their beloved uncle Chacko Rhodes scholar, pickle baron, radical Marxist, bottom-pincher, their enemy, Baby Kochamma ex-nun and incumbent grandaunt, and the ghost of an imperial entomologist\\\'s moth with unusually dense dorsal tufts. When their English cousin, Sophie Mol, and her mother, Margaret Kochamma, arrive on a Christmas visit, Esthappen and Rahel learn that Things Can Change in a Day. That lives can twist into new, ugly shapes, even cease forever, beside their river \\\graygreen. With fish in it. With the sky and trees in it. And at night, the broken yellow moon in it.\\\